Pembuatan Gim "Equilibrista" untuk Melatih Keterampilan Mengetik Pengguna Komputer - Aditya Victory Winata (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
This study aims to create a game application that can be used to practice typing skills, so that typing errors that occur when using keyboard are expected to be reduced. The method used to develop games in this research is Game Development Life Cycle (GDLC), and the game engine used is Unity, with C# as the programming language. User or beta testing was carried out on 10 early users to get input about the Equilibrista game. From the results of the tests, regarding the statement that the Equilibrista game can be a fun typing practice tool, 10% of respondents answered netral, 90% of respondents answered agree. Regarding the reduction of typos after playing the game Equilibrista, as many as 10% of respondents answered strongly disagree, 20% of respondents answered disagree, and 70% of respondents agree.